Effect of intermittent normobaric hypoxic exposure at rest on haematological, physiological, and performance parameters in multi-sport athletes - Hamlin, M. J.; Hellemans, J. (Journal of Sports Sciences, 2007)
The aim of this study was to determine whether 3 weeks of intermittent normobaric hypoxic exposure at rest was able to elicit changes that would benefit multi-sport athletes. Twenty-two multi-sport athletes of mixed ability were exposed to either a normobaric hypoxic gas (intermittent hypoxic training group) or a placebo gas containing normal room air (placebo group). The participants breathed the gas mixtures in 5-min intervals interspersed with 5-min recovery periods of normal room air for a total of 90 min per day, 5 days per week, over a 3-week period. The oxygen in the hypoxic gas decreased from 13% in week 1 to 10% by week 3. The training and placebo groups underwent a total of four performance tests, including a familiarization and baseline trial before the intervention, followed by trials at 2 and 17 days after the intervention. Time to complete the 3-km run decreased by 1.7%[95% confidence interval (CI) = -0.6 - 3.9%] 2 days after, and by 2.3% (CI = 0.25 - 4.4%) 17 days after, the last hypoxic episode in the training relative to the placebo group. Substantial changes in the training relative to the placebo group also included increased reticulocyte count 2 days (23.5%; CI =-1.9 to 44.9%) and 12 days (14.6%; CI = -7.1 to 36.4%) post-exposure. The effect of intermittent hypoxic training on 3-km performance found in this study is likely to be beneficial, which suggests non-elite multi-sport athletes should expect such training to enhance performance.